On the prospects of the beet sugar manufacture in Ireland - Hancock, W. Neilson (Dublin Statistical Society, 1851)
It was the great importance attached to the beet-sugar manufacture by some advocates of its introduction, which led me to direct my attention to the economic conditions necessary to its success. It is necessary to obtain answers to three entirely distinct and independent questions. First, What is the price of beet-root likely to be in Ireland for a series of years? Secondly, What is the price of refined beet-sugar likely to be in Ireland for the same period? Thirdly, Will it be profitable to manufacture from beet-root at the Irish prices, refined beet-sugar, to be sold at the price of that commodity in Ireland?
Read June 16th 1851
Keywords: Sugar beet; Agricultural production; 314.15